The Relationship between Perfectionism and Mental Toughness Among Athletes - Nazia Nisar; Atif Rasool; Umara Sameer; Ayesha Rehman; Sana Ameen (Research Journal of Psychology, 2025)
The purpose of this study is to explore the relationship between perfectionism and mental toughness among athletes. Athletes often face psychological pressures that can impact their emotional stability and mental resilience in high-performance sports environments. perfectionism was able to push an athlete to be good, it can foster stress or burnout as well, even leading to the failure of the athlete. On the other hand, mental toughness helps athletes to concentrate, be strong, and composure when pressurized. A correlational research design was used in the study and the sample size was purposively composed of 150 athletes between and aged 18 and 37. There were two standardized self-report questionnaires completed (Perfectionism Performance Scale-Sport (PPS-S12) and Sports Mental Toughness Questionnaire (SMTQ-14). Descriptive statistics, Pearson correlation and a simple linear regression was used to analyze the data. he findings indicated a significant positive correlation between perfectionism and mental toughness. A regression analysis indicated that perfectionism was a significant predictor of mental toughness with 50.3 per cent being explained. It has implications for clinical and sports psychologist, coaches and trainers in creating interventions and training programs to add at least mental resilience. Future studies should discriminate between adaptive and male adaptive perfectionism to more clearly understand their distinctive contribute mental toughness. Limitation national and international athletes should have already had built in greater psychological strength through experience this might impact outcomes.